1994
DOI: 10.1007/bf00354321
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induced by copper: defense and damage in the marine planktonic diatom Ditylum brightwellii, grown in continuous cultures with high and low zinc levels

Abstract: Light-limited cultures of the planktonic diatomDitylum brightwellii (West) Grunow were grown at 14%o salinity. Cells were subjected to oxidative stress induced by copper, in the presence of zinc. In two continuous cultures with total Zn levels of 40 and 140 nM, respectively, dissolved Cu levels were increased from 3 to 126 nM. This resulted in an increased Cu adsorption capacity of the cell walls, probably due to an increase of surface area and roughness. Sexual reproduction (auxospore formation) was accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 47 publications
5
52
0
Order By: Relevance
“…Enteromorpha, which is frequently used as an indicator species for heavy metal contamination, contained relatively great concentration of Cu (Rijstenbil et al, 1998a,b). The chelation removal of heavy metals from the cell surface after the binding of Cu with organic complexes (including cell exudates) is another possible mechanism for the detoxification of metal ions (Xue et al, 1988;Xue and Sigg, 1990;Rijstenbil et al, 1994;Gerringa et al, 1995).…”
Section: Bioconcentration Factor Of Cumentioning
confidence: 99%
See 1 more Smart Citation
“…Enteromorpha, which is frequently used as an indicator species for heavy metal contamination, contained relatively great concentration of Cu (Rijstenbil et al, 1998a,b). The chelation removal of heavy metals from the cell surface after the binding of Cu with organic complexes (including cell exudates) is another possible mechanism for the detoxification of metal ions (Xue et al, 1988;Xue and Sigg, 1990;Rijstenbil et al, 1994;Gerringa et al, 1995).…”
Section: Bioconcentration Factor Of Cumentioning
confidence: 99%
“…Binding to organic complexes, especially cell exudates, is another possible mechanism regulating the detoxification of metal ions (Xue et al, 1988;Xue and Sigg, 1990;Rijstenbil et al, 1994;Gerringa et al, 1995). It has been reported that microalgal production of glutathione, thiols or superoxide dismutase activity (SOD) can be stimulated by copper, which may also be a defense mechanism against copper toxicity (Rijstenbil et al, 1994(Rijstenbil et al, , 1998aRijstenbil and Wijnholds, 1996;Okamoto and Colepicolo, 1998;Leal et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Chi a fluorescence measurements show a site of Cu inhibition on the PS II antenna (Lidon and Henriques, 1993). Cu was also shown to be competing for other physiological metal ion sites, like Ca, at PS II, and that it may induce electron transport at PS II (Rijstenbil et al, 1994;Patsikka et al, 1998a,b). Time-resolved fluorescence decay analysis showed that Cu does not affect primary charge separation but destabilizes the charge stabilization (Yruela et al 1996b).…”
Section: B Copper (Cu)mentioning
confidence: 96%
“…As seen in algae (Scenedesmus sp. ), the binding of metals to thiols can protect cell metabolism from metal toxicity only temporarily; however, during severe stress, depletion of thiol pool is known to make cells vulnerable to oxidative stress (Rijstenbil et al 1994). Depletion of thiol content in Scenedesmus sp.…”
Section: Thiols/glutathionementioning
confidence: 99%